Estrategias metodológicas y su influencia en el desarrollo del lenguaje en educación inicial, subnivel 2 de la Escuela de Educación Básica Victor Manuel Villamarin - Velasco Naranjo, Masiel (2023)
Currently, methodological strategies are fundamental tools that serve as a model of planned activities by the teacher to strengthen the learning, language and oral expression capacity of their students. The research is carried out with the purpose of determining the methodological strategies and their influence on the development of language in initial education sublevel 2 of the “Víctor Manuel Villamarin Gómez” School of Basic Education. The study has a mixed approach and the types of research implemented were: documentary and descriptive. On the other hand, the research techniques applied were a interview and observation, for which it was necessary to apply the instruments: observation sheet, in which parameters related to language development were evaluated. While the interview guide was used with the purpose of knowing, the methodological techniques used to promote adequate language development. The results of the research allowed us to conclude that language development in early education plays a fundamental role in the comprehensive development of children, because it not only allows them to acquire vocabulary and grammar, but also helps them explore the world around them, express their thoughts, emotions and needs, and establish meaningful connections with others. It is recommended that teachers diversify teaching strategies in order to maintain children's interest.